A QUALITATIVE ANALYSIS OF CONSUMER BUYING INTEREST ON LOCAL COSMETIC PRODUCTS IN MANADO - Wereh, Astri S.; Tumbuan, Willem J. F. A.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Â The consumer's buying interest is a mental statement of consumers that reflects plan for purchasing a product with certain brands of knowledge about consumer buying intention for the product needs to be known by marketers for describe consumer behavior in the future.The aim of this study is to analyze the consumer buying interest on local cosmetic products in Manado. In order to achieve these objectives the researcher got information from 10 respondents who have been buying and using local cosmetic product and those who have an experience using local cosmetic products also using qualitative study which is in-depth interview and uses purposive sampling. The results showed that The buying interest of local cosmetic product is still high, all the informants that have been interviewed before gave a good opinion about the local cosmetics product, Based on interiew from all the informants also it can be conclude that the buying interest was still high even there are many foreingt cosmetics product that sell in the market, because the local cosmetics product most of the informant has already trust the local cosmetics product. The recommendation, for the consumer, it is good for the consumer to know about the consumer buying interest toward them and what factors that leads them to use local cosmetic product.Â Keywords: buying interest, local cosmetic product, qualitative analysis